STRUKTUR MIKRO CORAN KOMPOSIT Al 6061 + ABU BATUBARA SETELAH PERLAKUAN T6 - Ahmad, Zainun; Santoso, Edi (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2016)
Heat treatment on the aluminum alloy is done by heating until a singlephase was then arrested a few moments and forwarded by rapid cooling to nothave time to change to another phase. If the material was left for a certainperiod of time then there was the process of aging (aging). Changes will occurin the form of precipitation (precipitation) The second phase begins with theonset of nucleation and atom clusters that became the beginning of theprecipitates. This precipitates can increase the strength and hardness. Thisprocess is the age hardening process called natural aging. If after rapid coolingthen heated again to below the solvus temperature (solvus line) then detained inthe long term and followed by slow cooling in the air called artificial agingprocess (artificial aging). This study aims to determine the microstructure ofwhat is formed from a material with a temperature variation of aging (200oC,225oC, 250oC) and holding time (8 hours, 12 hours, 16 hours) to determine howmuch influence the variables, can be analyzed through testing SEM EDXA.From the test results of SEM-EDXA it can be determined microstructure formedin 6061 + Al composite coal bottom ash, which is composed of aluminum oxidecompound of Al 2 O 3 and MgO.Keywords: microstructure, composites, coal bottom ash